Labour Migration as One of The Factors Influencing Economic Security - Izabela Szkurlat (Communications of International Proceedings, 2020)
Maintaining economic security is one of the foundations of the functioning of the state. It also relates to the security of the national economy and the threats associated with it. We assume that the economy must generate profits and function smoothly. The problem of an ageing population and shortages of human resources may affect its disruption. Labour migration may be the solution. One of the aims of this article is a statistical analysis which shows the scale of economic migration of Poles to other countries, including Europe. This affects the Polish labour market and the need to fill it with economic migrants from other countries.
Keywords: Economic Security; Labour Migration; Emigration; Immigration